Microeconomic theory and applications - Browning, Edgar K.; Browning, Jacquelene M. (Glenview, Illinois : Scott, Foresman and Company, 1989)
The study of how markets operate is the cornerstone of microeconomics theory, and understanding how markets operate is essential to understanding how our economic system functions. Beyond developing a coherent view of economic reality, microeconomics provides techniques that increasingly play roles in both public policy formulation and private decision making.
1. Microeconomic and Market Analysis -- 2. The Theory of Consumer Choice -- 3. Individual and market Demand -- 4. Using Consumer Choice Theory -- 5. Exchange, Efficiency, and Prices -- 6. Production -- 7. The Cost of Production -- 8. Profit Maximization and the Competitive Firm -- 9. The Competitive Industry -- 10. Using the Competitive Model -- 11. Monopoly -- 12. Using Monopoly Theory -- 13. Monopolistic Competition and oligopoly -- 14. employment and Pricing of Inputs -- 15. Wages, Rent, Interest, and Profit -- 16. Using Input market Analysis -- 17. General Equilibrium Analysis -- 18. Welfare Economics -- 19. Public Goods and Externalities.
Includes index.
Keywords: MICROECONOMICS